Philosophy for Children at the Level of the Philosophy Science and the Authorization of the Islamic Teaching - Zohreh Tavaziani; Ali Sattari (آموزه‌‌های فلسفه اسلامي, 2022)
Matthew Lipman, the founder of the concept of philosophy for children, has selected the title of philosophy in the philosophy educational program for children different from the general philosophers’ understanding (perception). As far as it can be said that this concept basically cannot be situated in the semantic sphere of the philosophy or it is to a more limited extent than it. The present note with the descriptive-analytic method aims to study the philosophy program for children in relation to and at the level with the position of the philosophy science with emphasizing two components of meaning and subject of philosophy. Also, from the point of the Islamic teaching which teaching system of our country with following and influence of it is formed, it examines its necessity or unnecessity of philosophy teaching for children and its priority, too. The result shows that the philosophy meaning and subject matter in “philosophy for children” is different from its current meaning and subject matter in philosophy science which is being qua being. The subject matter of philosophy in philosophy for children is not going beyond the natural and social environment. Because this program emphasizes not paying attention to metaphysic subjects and issues. While metaphysics and its issues such as the issue of God have been of the basic subjects and it is the pivot of Islamic education. Also, the outcomes of the research show that there is no direct recommendation and order for philosophy teaching in Islamic education. But from the other side, it is not prohibited philosophizing. However, the priority of teachings in Islamic education is not philosophy teaching; the priority is to teach. but the priority is to teach the fundamental beliefs of Islam, religious beliefs, Islamic ethics and manners and training children. Therefore, philosophy for children is not in priority in the Islamic educational system.